2011
DOI: 10.1039/c1cc11135c
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed C–H bond functionalization of C6-arylpurines

Abstract: A highly regioselective Pd-catalyzed C(Ar)-H bond activation method was developed for the modification of purines (nucleosides) with different functional groups by using purine as a directing group. This approach provides a new access to a variety of functionalized purines (nucleosides) which are potentially of great importance in medicinal chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…18 There, oxidation of 6-phenyl-9-(2,3,5-tri- O -acetyl- β -D-ribofuranosyl)purine gave mono- as well as diacetoxylated products in a ~2.1:1 ratio (combined 77% yield). 18 This substrate, being a ribonucleoside and bearing electron-withdrawing acetate protecting groups on the saccharide, proved to be relatively stable in acetic acid at 120 °C. These conditions, however, are likely to be incompatible with more sensitive substrates.…”
Section: Results and Discissionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 There, oxidation of 6-phenyl-9-(2,3,5-tri- O -acetyl- β -D-ribofuranosyl)purine gave mono- as well as diacetoxylated products in a ~2.1:1 ratio (combined 77% yield). 18 This substrate, being a ribonucleoside and bearing electron-withdrawing acetate protecting groups on the saccharide, proved to be relatively stable in acetic acid at 120 °C. These conditions, however, are likely to be incompatible with more sensitive substrates.…”
Section: Results and Discissionmentioning
confidence: 99%
“…18 Thus, palladated dimers such as 10 , which can potentially form in the reaction, are competent in catalyzing the oxidation reaction. The plausible involvement of 10 in the catalytic cycle is shown in Scheme 1.…”
Section: Results and Discissionmentioning
confidence: 99%
See 1 more Smart Citation
“…ortho ‐Alkoxylation of 9‐butyl‐6‐phenylpurine and 9‐benzyl‐6‐phenylpurine has been performed with Pd(OAc) 2 /PhI(OAc) 2 at 100 °C [Equation ].…”
Section: Purinyl Coordinating Groupsmentioning
confidence: 99%
“…36 It has recently been quantitatively shown that 2′-deoxyribonucleosides are substantially more labile as compared to the ribosyl counterparts. For example, the t 1/2 for the deglycosylation of adenosine in 0.1 M HCl is 11 days at 37 °C.…”
Section: Purinyl N-directed C–h Bond Oxidation Using Pidamentioning
confidence: 99%